Efficacy and safety of modified bleomycin administration with EP chemotherapy in adult male patients with germ cell tumors: a retrospective study - Ditian Shu; Riqing Huang; Meiting Chen; Haifeng Li; Xin An; Cong Xue; Anqi Hu; Fangjian Zhou; Kai Yao; Zhuowei Liu; Yanxia Shi (Cancer Cell International)
Abstract Background Given the substantial inconvenience caused by weekly bleomycin administration, we initiated a study to evaluate the efficacy and toxicity of the modified bleomycin combined with EP (modified-BEP) regimen in Chinese adult male patients with germ cell tumors (GCTs). Methods We conducted a retrospective analysis of 274 adult male GCT patients treated with modified-BEP at the Sun Yat-sen University Cancer Center between 2005 and 2022. The regimen involved a tri-weekly 5-day schedule with 30 IU modified bleomycin (administered on days 1, 3, and 5), 20 mg/m2 cisplatin (days 1–5), and 100 mg/m2 etoposide (days 1–5). The survival rates and safety profiles of the patients were analyzed. Results Among the patients, 42 patients received BEP in adjuvant setting, while 232 were treated with BEP in curative setting. With a median follow-up of 41.03 months among the curative patient population, the 5-year progression-free survival (PFS) rate was 79.33%, and the 5-year overall survival (OS) rate was 86.26%. Stratified by the International Germ Cell Cancer Collaborative Group (IGCCCG) prognostic groups, the 5-year OS rates of the good, intermediate, and poor risk groups were 99.05%, 92.84%, and 55.96% (P < 0.0001), respectively. Favorable responses, including complete remission and partial response with negative tumor markers, were achieved in 91.07% of good-risk, 84.13% of intermediate-risk, and 52.63% of poor-risk patients, with a significant difference (P < 0.0001). Multivariate analysis indicated that non-seminoma, poor risk group, mediastinal primary tumor, and Eastern Cooperative Oncology Group (ECOG) 2 status were significantly associated with inferior PFS. In the entire cohort, major grade 3—4 adverse events included neutropenia (38.69%), anemia (4.74%), thrombocytopenia (5.11%), and febrile neutropenia (6.2%), with no death due to pulmonary toxicity. Conclusion The modified-BEP regimen showed an effective and tolerable treatment alternative for adult male GCT patients in China, offering greater convenience compared to the standard BEP regimen.